Subjects with temporomandibular joint disc displacement do not feature any peculiar changes in body posture. (February 2017) - Rocha, T.; Castro, M. A.; Guarda‐Nardini, L.; Manfredini, D.
Summary: The presence of body posture changes among patients with temporomandibular disorders (TMD) has been a controversial topic in dentistry. Based on that, the aim of this study was to assess postural features of pain‐free subjects with internal derangement of the temporomandibular joint (TMJ), viz. disc displacement, when compared to subjects with normal disc position. A total of 21 subjects with unilateral, pain‐free TMJ disc displacement (DD) and 21 subjects without any TMD signs of symptoms were assessed for body posture changes by means of posturographic evaluation of several body segments and postural balance reactions through the centre of mass during jaw movements using a balance platform. Posturographic measurements showed the absence of any significant differences between the two groups in any of the outcome parameters. Similarly, all balance platform responses to mandibular movements were not different between groups. There are no significant differences in body posture between subjects with and without unilateral disc displacement in the temporomandibular joint. Such observations, indicating a well‐preserved postural balance in the presence of TMJ internal derangement, put into serious question the potential influence of TMJ disorders on whole body posture and viceversa.